Plating Techniques of Sweet Potato Condiments in Main Course Practicum - Witara, I Made; Nugroho, Setyo Prasiyono; Achmad Taufiq (Gastronomy and Culinary Art, 2026)
Food plating is a key element in hospitality standards, as visual presentation influences perceived quality and professionalism. This study explores the application of plating techniques using sweet potato-based condiments (mash and wedges) as alternatives to potato in main course practicum at STP AMPTA Yogyakarta. A qualitative case study approach was employed, with data collected through observation, interviews, and documentation, and analyzed using the Miles, Huberman, and Saldaña model. The findings show that sweet potato innovation serves as an effective medium for integrating local ingredients into international presentation standards while enhancing students’ mastery of basic culinary techniques. Students demonstrated the ability to apply plating principles such as proportion, color harmony, balance, and composition. However, inconsistencies in mash texture and wedge doneness affected plating outcomes. Supporting factors include adequate facilities, instructor guidance, and repeated practice, while constraints involve time limitations, limited tools, and varying skill levels. Overall, this approach improves technical, aesthetic, and local ingredient awareness in hospitality education.